Subarachnoid clonidine and trauma response in cardiac surgery with cardiopulmonary bypass - Ferreira,Claudia Gissi da Rocha (2014)
Background and objectives: The intense trauma response triggered by cardiopulmonary bypass can lead to increased morbidity and mortality. The present study evaluated whether clonidine, a drug of the class of α-2 agonists, administered by spinal route, without association with local anesthetics or opioids, reduces this response in cardiac surgery with cardiopulmonary bypass. Method: A total of 27 patients between 18 and 75 years old, divided by non-blinded fashion into a control group (15) and a clonidine group (12), were studied. All patients underwent identical technique of general anesthesia. Then, only the clonidine group received 1 μg kg−1 clonidine by spinal route. Levels of blood glucose, lactate and cortisol were measured at three consecutive times: T1, at the time of installation of invasive arterial pressure; T2, 10 min after the first dose for cardioplegia; and T3, at the time of skin suture; and troponin I values at T1 and T3. The variation of results between T2-T1, T3-T2, and T3-T1 was also evaluated. Results: There was a statistically significant difference only with respect to the variation in blood glucose in the clonidine group: T3-T2, p = 0.027 and T3-T1, p = 0.047. Conclusions: Spinal clonidine at a dose of 1 μg kg−1 did not decrease blood measurements of troponin, cortisol, or lactate. Blood glucose suffered a more moderate variation during the procedure in the clonidine group. This fact, already reported in the literature, requires further investigation to be clarified.